STRUKTUR DAN FUNGSI PANTUN DALAM ACARA MANYERAKAN MARAPULAI DAN ANAK DARO PADA UPACARA PERNIKAHAN DI DESA TABEK SIRAH KABUPATEN PASAMAN BARAT - Rina Handayani; Agustina Agustina; Hamidin Hamidin (Faculty of Languages and Arts, Universitas Negeri Padang, 2014)
The purpose of this study was to describe the structure and function of the poem in the event manyerakan marapulai and children daro at the wedding ceremony in the village of West Pasaman Tabek Sirah. This research is descriptive qualitative research method. The object of research in the form of rhymes and children's events manyerakan marapulai and children daro. Data analysis was performed with (1) transcripts of recording data into written language, (2) analyzing the data, (3) to classify the data into the aspects studied, (4) interpreting the data in accordance with the purposes of the study, (5) make the conclusion. The results of this study indicate that in the event manyerakan marapulai rhymes and children daro has a physical structure and inner structure. The physical structure consists of : diction, imagery, concrete words, figurative language, rhyme and Rithmah, while the inner structure consists of : theme, feeling, tone and atmosphere and mandate. Functions contained in the event manyerakan marapulai rhymes and children daro found ten functions, namely (1) as a means of communication, (2) the identity, (3) as an ornamental flower oral tradition, (4) as a means to preach, (5) as a means to educate, (6) as the embodiment of indigenou , (7) as a means of entertainment, (8) as symbols of culture, (9) evokes heroic values ​​and (10) to further humanize humans.